Efficacy and safety of lenvatinib plus gefitinib in lenvatinib-resistant hepatocellular carcinomas: a prospective, single-arm exploratory trial - Yaoping Shi; Dan Cui; Lei Xia; Donghua Shi; Guangxin Jin; Siying Wang; Yan Lin; Xiaoyin Tang; Jiachang Chi; Tao Wang; Meng Li; Zicheng Lv; et al. (Signal Transduction and Targeted Therapy)
Abstract Lenvatinib, a multi-kinase inhibitor, has been approved as first-line treatment for advanced hepatocellular carcinoma (HCC), but its efficacy is limited. We have shown previously that lenvatinib and epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) combination therapy overcomes lenvatinib resistance in HCC with high level of EGFR expression (EGFRhigh). We present here the results of a single-arm, open-label, exploratory study of lenvatinib plus the EGFR-TKI gefitinib for patients with HCC resistance to lenvatinib (NCT04642547; n = 30). Only patients with EGFRhigh HCC and progressive disease after lenvatinib treatment were recruited in the study. The most frequent adverse events of all grades were fatigue (27 patients; 90%), followed by rash (25 patients; 83.3%), diarrhea (24 patients; 80%), and anorexia (12 patients; 40%). Among 30 patients, 9 (30%) achieved a confirmed partial response and 14 (46.7%) had stable disease according to mRECIST criteria. Based on RECIST1.1, 5 (16.7%) achieved a confirmed partial response and 18 (60%) had stable disease. The estimated median progression free survival (PFS) and overall survival (OS) time were 4.4 months (95% CI: 2.5 to 5.9) and13.7 months (95% CI: 9.0 to NA), respectively. The objective response rate (ORR) of the patients in the present study compares very favorable to that seen for the two approved second line treatments for HCC (cabozantinib ORR of 4%; regorafenib ORR of 11%). Given that this combination was well-tolerated, a further clinical study of this combination is warranted.